The business of choice : how human instinct influences everyone's decisions - Willcox, Matthew (Emerald Publishing Limited, 2020)
In this 2nd edition of award winning The Business of Choice, expert author and consultant Matthew Willcox explores the science of influencing choice, bringing together the work of thousands of behavioral scientists and practitioners. Cutting to the heart of the science, Willcox helps you apply this to your own marketing and brand strategies, allowing you to use an understanding of how humans naturally decide to make your brand or business a natural choice. The Business of Choice takes you through the story of how instinct affects our decisions, from its roots in our evolutionary history, to technology and artificial intelligence today. You'll discover how human nature affects how people decide, whether they are making choices for grocery shopping, or their retirement investments. The first edition of The Business of Choice was awarded the 2016 Berry - American Marketing Association Book Prize for Best Book in Marketing.